2018
DOI: 10.1016/j.rboe.2017.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Biplanar carpal wedge osteotomy in the treatment of the arthrogrypotic patients

Abstract: ObjectiveTo describe the results of the surgical treatment of patients with congenital arthrogryposis with wrist deformity through biplanar carpal wedge osteotomy.MethodThis study analyzed nine patients through a retrospective evaluation with severe deformity in flexion and ulnar deviation of the wrist in the period between January 2004 and December 2009. They were submitted to carpal osteotomy with a biplanar dorsal resection wedge, with a minimum evaluation of 48 months of postoperative evolution. In three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…In addition, the authors found significantly greater improvement in those children operated on after the age of 7 and in those who underwent concomitant ECU tendon transfer (Van Heest & Rodriguez, ). Finally, De Oliveira et al found similar improvements in wrist position with little change in total arc of motion following carpal wedge osteotomy (Oliveira et al, ).…”
Section: Wristmentioning
confidence: 89%
“…In addition, the authors found significantly greater improvement in those children operated on after the age of 7 and in those who underwent concomitant ECU tendon transfer (Van Heest & Rodriguez, ). Finally, De Oliveira et al found similar improvements in wrist position with little change in total arc of motion following carpal wedge osteotomy (Oliveira et al, ).…”
Section: Wristmentioning
confidence: 89%